Student Perceptions of Generative AI (GenAI) Use in Academic Writing: A Case Study of an EAP Module at XJTLU (Contemporary Education and Teaching Research, 2026)
This research employed a case study design to explore students’ perceptions of Generative AI (GenAI) use in academic writing. Participants were 33 first-year undergraduates enrolled in an EAP module at a Sino-British university. Data were collected via an online survey and semi-structured interviews. Findings indicated generally positive attitudes toward AI-enabled writing tools, with students acknowledging their benefits in improving writing quality and streamlining processes. However, participants demonstrated critical awareness of risks, such as GenAI over-reliance and the potential erosion of core academic skills. Adoption of GenAI was widespread, with a clear preference for locally accessible tools like Doubao, favored for its affordability and accessibility. Students held nuanced stance across studied dimensions: they strongly endorsed GenAI’s utility and efficiency, yet expressed considerable ethical concerns. Lower ratings for quality and reliability, along with concerns about cognitive impact, suggested an underlying skepticism shaping their pragmatic adoption. No significant differences in perception were found based on gender or academic background. In response to students’ expressed needs for support, this study proposes an integrated framework encompassing pedagogical, operational, and ethical dimensions through which teachers, academic staff, and policymakers can collaborate. The findings suggest that the central challenge for higher education lies not in whether to prohibit or promote GenAI, but in cultivating AI-literate learners who can harness technological affordances while safeguarding the critical thinking and ethical judgment essential to meaningful education.